KEANEKARAGAMAN â€œKOMUNITAS BAWAHâ€ KAWASAN PERKEBUNAN TEH DI GUNUNG DEMPO, KOTA PAGARALAM, SUMATERA SELATAN - Iswantono Tono; Didi Jaya Santri; Riyanto Riyanto (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abstract: The research on the species diversity of â€œunder communityâ€ Tea plantations in Region Pagaralam has done that aims to identify and describe the different types of morphological characteristics of each species of plants and animals found. Research using descriptive methods. Sampling of plants was done by Sampling Purvosve Method. Sampling of animals was done pitfall trap and light trap. Sampling The results of the qualitative analysis of plants and animals are found as many as 92 species consist of 39 species of plants and 53 species of animals. Plants were found to consist of 29 species of Magnoliophyta, 6 species of Pteridophyta and Bryophyta 4 species. Animals were found to consist of 47 kinds of Arthropods, three species of chordates, two species of molluscs and 1 species of annelids. Under Community's existence is found to have a role as the respective components of the ecosystem such as producers, consumers and decomposers. The results of this study are expected to be used as basic data and information in learning in high school biology class X KD 4.9 Designing a chart of the interaction between the components of the ecosystem and food networking that takes place in the ecosystem and presenting the results in various forms of media Key words: diversity, under Comunity, tea Plantations Pagar Alam.